2016
DOI: 10.1007/s00192-016-3017-5
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injury: a follow-up questionnaire study on longer-term outcomes

Abstract: In this study, women with OASIS had a more than doubled risk of longer-term bothersome symptoms of AI compared with controls. Symptoms were experienced as bothersome and as having an influence on QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Cesarean delivery is related to respiratory neonatal morbidity and there is an increasing focus on a possible association between cesarean delivery and long‐term immunologic morbidity . On the other hand, planned vaginal delivery imposes a risk of OASISwith the reported incidence of anal incontinence wide‐ranging from 7% to 61% …”
Section: Discussionmentioning
confidence: 99%
“…Cesarean delivery is related to respiratory neonatal morbidity and there is an increasing focus on a possible association between cesarean delivery and long‐term immunologic morbidity . On the other hand, planned vaginal delivery imposes a risk of OASISwith the reported incidence of anal incontinence wide‐ranging from 7% to 61% …”
Section: Discussionmentioning
confidence: 99%
“…Fecal urgency is defined as having difficulty deferring a sudden or compelling desire to defecate. 5,14,[16][17][18][19][20] The role of planned CS in order to prevent OASIS, AI, and the potential impact of delivery on women's future health remains unclear 1,7,21 A Cochrane Review concluded that planned CS showed no benefit in the prevention of AI in postpartum women. 2,12,13 Furthermore, other studies have shown that AI, in particular, may have a devastating impact on women's social, emotional, and physical activity as well as their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 AI is associated with increasing age, obesity, pregnancy, instrumental VD, and obstetric anal sphincter injury (OASIS). 5,14,[16][17][18][19][20] The role of planned CS in order to prevent OASIS, AI, and the potential impact of delivery on women's future health remains unclear 1,7,21 A Cochrane Review concluded that planned CS showed no benefit in the prevention of AI in postpartum women. 7 The aim of this study was to explore whether women who only had delivered vaginally were at greater risk of developing AI than women who had undergone only cesarean sections or women who had never experienced childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Cornelisse et al in the Netherlands found that 39% of women with OASIS suffered from anal incontinence four years postpartum, as compared to 20% of women who delivered vaginally without OASIS (19). Cornelisse et al found that most of the women suffered from leakage of atus, 31% of the women with OASIS and 18% of the women without OASIS experienced this.…”
Section: Andrews Et Al Found That 14% Of Women Who Deliver Vaginally mentioning
confidence: 99%